PEMETAAN PENELITIAN SEPUTAR KESETARAAN GENDER PADA PERTANIAN: STUDI BIBLIOMETRIK VOSVIEWER DAN LITERATURE REVIEW - Putri, Mitha Octaviani; Aulia, Adinda; Syahrizal, Azwin; Wati, Dewi Rohma (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
This study investigates gender equality in agriculture using bibliometric analysis and literature review methods. A total of 54 articles indexed in SINTA (2014–2024) were analyzed using VOSviewer software to visualize collaboration networks, thematic trends, and publication patterns. Bibliometric metrics, including H-index, G-index, and citation counts, were calculated using Publish or Perish software. The findings reveal persistent gender inequality in agriculture, reflected in uneven labor distribution, decision-making biases, and limited access to resources for women. Women's significant contributions often remain underrecognized. By combining quantitative bibliometric analysis with qualitative insights from literature, this study provides a comprehensive understanding of gender issues in agriculture and offers evidence-based recommendations for developing inclusive, gender-sensitive policies to foster sustainability and equity in the agricultural sector.